2002
DOI: 10.1176/appi.ajp.159.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender on Attention Deficit Hyperactivity Disorder in Children Referred to a Psychiatric Clinic

Abstract: The lower likelihood for girls to manifest psychiatric, cognitive, and functional impairment than boys could result in gender-based referral bias unfavorable to girls with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
415
12
24

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 687 publications
(501 citation statements)
references
References 23 publications
50
415
12
24
Order By: Relevance
“…In the subset of these participants with known IQ>80, this proportion was 8/21 (38%). The rate of anxiety disorders in children with ADHD, IQ>80, and no epilepsy has been reported by Biederman et al as 30% in a sample of 280 children [11]. Eleven participants in the present study had ODD (31%).…”
Section: Comorbid Psychiatric Disorderssupporting
confidence: 64%
See 1 more Smart Citation
“…In the subset of these participants with known IQ>80, this proportion was 8/21 (38%). The rate of anxiety disorders in children with ADHD, IQ>80, and no epilepsy has been reported by Biederman et al as 30% in a sample of 280 children [11]. Eleven participants in the present study had ODD (31%).…”
Section: Comorbid Psychiatric Disorderssupporting
confidence: 64%
“…The rate of comorbidity between ADHD and Oppositional Defiant Disorder (ODD) is about 50%, Conduct Disorder about 15%, and anxiety disorders about 30% [11], and between ADHD and MDD between 14 to 44% [12]. Children with ADHD without epilepsy are commonly male and display the combined subtype.…”
Section: Introductionmentioning
confidence: 99%
“…Biederman et al 47 recently reported no significant differences between male and female subjects in the rate of any of the ADHD symptoms in a sample of non-referred children, suggesting that the gender differences identified previously in referred ADHD subjects 48 could represent an artifact of referral bias rather than true gender effects. Our data confirm this finding in a sample of obese adolescents who were not specifically referred for ADHD symptoms.…”
Section: Adhd and Bulimic Symptoms In Obese Children S Cortese Et Almentioning
confidence: 92%
“…Earlier studies of clinical populations of ADHD have repeatedly shown gender differences in outcomes 17, 65, 66. Some indicate that girls with ADHD can have severe psychiatric comorbidities and low global functioning 67, 68, 69, 70, while others have shown that girls can be less impaired than boys 5.…”
Section: Discussionmentioning
confidence: 99%
“…ADHD affects both boys and girls in all areas of functioning, for example, academically, cognitively, psychosocially, and psychiatrically 14, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30. Even though ADHD is associated with coexisting externalizing and internalizing disorders in both genders, girls with ADHD are significantly more likely to display internalizing disorders than boys with ADHD 25, 31, 32, 33.…”
Section: Introductionmentioning
confidence: 99%